Self-Cleaning Ability of Pollutants Containing Nitrogen and Phosphorus Transformed into NH4+, NO2-, NO3-, PO43-, of SonLa Hydropower Reservoir - Duc, Do Xuan; Hai, Luu Duc; Tuan, Do Huu (VNU Journal of Science: Earth and Environmental Sciences; Vol 36 No 3DO - 10.25073/2588-1094/vnuees.4510, 2020)
The waste source containing nitrogen (N) and organic phosphorus (P) into the hydropower reservoir will be transformed into pollutants NH 4 + , NO 2 - , NO 3 - , PO 4 3- . Son La hydropower reservoir has an area of ​​225 km 2 of water surface and 10,850 km 2 of water supply basin for electricity generation, Son La hydroelectricity plant and dam, which is particularly important in terms of socio-economic and national conditions, room, security. Using the method of calculating emissions with appropriate coefficients, 10.323 tons of nitrogen / year and 5.454 tons of phosphorus / year were added to the lake in 2019 through the data of population, livestock, fish cages, farming. Semi-submerged agriculture, depositing air into the lake. Applying the method of calculating the self-cleaning capacity of hydropower reservoirs through the results of determining the total main pollutants in the catchment tons N/P, the concentration of main pollutants in the water input and out of the lake, the concentration catchment pollutant (mg/L), basin pollutant input (tons / day), hydraulic retention time. Thereby, the Son La hydropower reservoir self-cleaning 8,117 tons / year with pollutants of groups NH 4 + , NO 2 - , NO 3 - , PO 4 3- , specifically a volume of 2,756 million m 3 and 16 days to save water. 1,224 tons were cleaned, a capacity of 6,504 million m 3 with 37 days to save water, the lake cleaned 2,856 tons, a capacity of 9,266 million m 3 , and a retention time was 52 days, the lake cleaned 4,037 tons.